THE INTERNET'S ROLE IN DIGITAL LEARNING AT DIFFERENT EDUCATIONAL LEVELS IN INDONESIA - Trimey Liria Hutauruk (Jurnal Scientia, 2022)
Integration of information and communication technology in the education sector demonstrates that, in the era of technological disruption, the optimization of internet usage is readily apparent. The real form of technical advancement is the existence of internet services that can serve as a bridge between the speed at which information may be received by all levels of society. The usage of the Internet as a learning tool is extremely beneficial and can have both positive and bad effects on pupils. Internet use has a significant impact on ensuring that the quality of education meets the requirements of the curriculum, and it also influences the learning patterns of students and teachers throughout Indonesia in order to improve the learning process. The goal of this study is to examine the distinctive educational function of the Internet in each region of Indonesia. The results revealed that 10% of students used the internet to support the learning process, with the majority of internet users for the learning process having a high school education or equivalent, indicating that the role of the internet in relation to digital learning adaptation requires the active participation of parents and teachers. In addition to allowing students to comprehend the positive and negative effects of the internet, the internet facilitates the production of interactive learning media and provides the most recent information to maximize digital learning platforms and develop innovative learning patterns in the digital age.